Nitrogen mineralization from organic fertilizers and composts: Literature survey and model fitting. Issue 6 (10th November 2021) - Geisseler, Daniel; Smith, Richard; Cahn, Mike; Muramoto, Joji
Abstract: Organic fertilizers and composts are valuable sources of nutrients. However, their nutrient availability is often not known and can be variable. The objective of the present study was to collect net nitrogen (N) turnover data from peer‐reviewed articles and fit a model that simulates gross N mineralization and gross N immobilization to determine pool sizes and their rate constants of different common organic amendments. A total of 113 datasets were included in the study. The model predicted that 61 and 72.5% of total N in feather meal and guano, respectively, would be in the mineral form after 100 d under optimal conditions. Nitrogen availability from poultry manure and poultry manure compost was lower. On average, 16–17% of total N was present as mineral N in the materials, whereas at the end of the 100‐d simulation, 39.6 and 32.7% of total N from an average poultry manure and its compost, respectively, were in the mineral form. Yard waste compost and vermicompost are stable materials, with <10% of the total N in an average material being in the mineral form at the end of the 100‐d simulation. Model simulations revealed that changes in the assumed temperature sensitivity of N mineralization have a strong effect on N availability of readily available organic amendments during the first weeks after incorporation. The model performed well for guano and feather meal but was unsatisfactory for the other amendment groups. Model performance may have been hampered by different incubation protocols used in the studies included and variability in amendment properties not considered by the model. The results of this study allow estimating the release of N from a variety of organic fertilizers and composts and can be a valuable tool to improve N management of organic amendments in crop production. Core Ideas:  A total of 113 datasets from peer review articles were compiled for this study.  60–75% of N in feather meal and guano are typically available within 100 d.  30–40% of N are available from poultry manure and its compost after 100 d.  Less than 10% of N in vermicompost and yard waste compost are available after 100 d.  The results help making N management decisions with organic amendments.